An unusual association of pyoderma gangrenosum with ulcerative colitis and thyrotoxicosis successfully treated with infliximab: a case report - Abualiat, Abdullah; Edris, Hala; Alfadni, Salaheldin; Aziz, Tariq; Hussein, Mahmoud (International Journal of Research in Medical Sciences, 2020)
Pyoderma Gangrenosum (PG) is a rare chronic immune-mediated inflammatory dermatosis manifested as painful skin ulceration, commonly affecting the lower limbs. The pathogenesis of the disease is complex. Abnormalities in neutrophil function, dysregulation of the innate immune system, and Tumor Necrosis Factor (TNF) were postulated. An underlying associated systemic disease was reported in more than 50% of PG patients, including inflammatory bowel disease, rheumatoid arthritis, and malignancies, with few cases reported an associated thyroid disease. Authors report a case of extensive PG associated with both ulcerative colitis and thyrotoxicosis co-morbidities not mentioned before in one patient. The patient was successfully treated with the anti-TNF alpha infliximab.